Method for manufacturing anode for lithium ion battery
By depositing a protective coating on the anode of the lithium-ion battery, the problem of lithium loss during the irreversible embedding and annealing of the lithium-ion battery during the first charge is solved, the stability and performance of the battery are improved, and the charging and discharging are achieved. Number of cycles and operating voltage range.
Patent Information
- Application Number
- CN201980029250.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-05-07
- Filing Date
- 2019-05-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2039-05-06
AI Technical Summary
The irreversible embeddedness of lithium in the anode material during the first charging of existing lithium-ion batteries leads to capacity loss, and lithium loss and impurities during the annealing process of all-solid lithium-ion batteries interfere with battery operation and affect battery performance.
The protective coating is used to deposit dense coatings on the anode through atomic layer deposition technology (ALD) or chemical solution decomposition technology (CSD) to prevent lithium from reacting with the ambient atmosphere, and cover it with a solid electrolyte membrane to protect the anode material and ensure lithium ions reversible embedding and battery performance.
It effectively prevents the reaction between lithium ions and air or moisture, reduces the irreversible loss of the anode during the first charge, improves the number of charge and discharge cycles and working voltage range of the battery, and enhances the stability and performance of the battery.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary batteries, in particular to lithium-ion batteries. The present invention more particularly relates to thin-film lithium-ion batteries. The present invention relates to a new method for manufacturing anodes of these batteries. The present invention also relates to a method for manufacturing an electrochemical device, in particular a battery-type electrochemical device, comprising at least one of these anodes, and to the device obtained thereby. Background Art
[0002] The secondary lithium-ion battery obtained by the method of manufacturing a secondary lithium-ion battery is usually discharged: it includes an electrode embedded with lithium (the electrode is called the cathode) and an electrode without lithium ions (the electrode is called the anode). During the battery charging process, lithium ions are extracted from the cathode (which serves as the anode during the charging process) and migrate through the electrolyte to reach the anode (which serves as the cathode during the charging process), where the lithium ions are embedded in the structure of the anode material; the electrons circulating in the external charging circuit reduce the anode and oxidize the cathode. All reactions occurring at the electrodes must be reversible so that the battery can achieve a large number of charge and discharge cycles.
[0003] In all-solid-state lithium-ion batteries, since these cells do not contain any liquid phase, the transport of lithium ions in the electrolyte and electrodes occurs by diffusion in the solid; in order to limit the series resistance of the device, the electrolyte and electrodes are usually in the form of thin films. The cells and the layers of the cells can be deposited by electrophoresis; this is known, for example, from patent applications WO 2013 / 064 772, WO 2013 / 064 773, WO 2013 / 064 774, WO 2013 / 064 776, WO 2013 / 064 779, WO 2013 / 064 781, WO 2014 / 102 520, WO 2014 / 131 997, WO 2016 / 001 579, WO 2016 / 001584, WO 2016 / 001 588, WO 2017 / 115 032 (I-TEN).
[0004] There are several specific issues that can occur with these batteries.
[0005] These batteries are manufactured in a discharged state, ie, all of the lithium is inserted into the cathode.
[0006] During the first charge, lithium will leave the cathode and intercalate into the anode; this causes an irreversible structural transformation within the anode. When a large amount of lithium remains irreversibly intercalated in the anode, the final capacity of the battery and its operating voltage range are slightly reduced.
[0007] In an attempt to compensate for the irreversible loss of the anode during initial charge, ie, this reduction in capacity, the capacity of the cathode may be made greater than that of the anode, or the cathode material may contain an excess of lithium after fabrication.
[0008] It is known that during the first charge of a battery, the anode has an irreversible loss. In other words, a portion of the lithium embedded in the anode material can no longer be released during the discharge of the battery. This loss is even more severe for anode materials of the nitride or oxynitride type.
[0009] For example, Park et al. published an article entitled "Characteristics of tin nitride thin-film negative electrode for thin-film microbattery" (Journal of Power Sources, Vol. 103, pp. 67-71, 2001) describing that the capacity of a lithium-ion battery during the first charge is about 750 μA h / cm 2 μm, and then stabilized at about 250 μA h / cm 2 To ensure good reversibility of the reaction at the electrode, for about 200 μAh / cm 2 μm capacity, it is necessary to comply with the working range of 0.2V to 0.8V. In this example, the anode is made of tin nitride. N. Kalaiselvi's article "Synthesis and Electrochemical Characterization of novel Category Si3-x MxN4 (M=Co,Ni,Fe) Anodes for rechargeable Lithium Batteries" (Int. J. Electrochem. Sci, Vol. 2 (2007), pp. 478-487) observed similar degradation in lithium-ion batteries with anodes made of silicon nitride, but it was not as obvious, in which part of the silicon in the anode could be replaced by Co, Ni or Fe.
[0010] Document WO2015 / 133139 (Sharp Kabushiki Kaisha) describes an anode pre-embedded with lithium, which can limit the impact of irreversible capacity loss during the first charge. However, the method described in the document is very difficult to implement because metallic lithium is highly reactive to the atmosphere and humidity. The method includes a step of mixing the anode material with lithium powder in argon, or a step of reducing the anode material with a lithium compound, or a step of electrochemically reducing lithium. After the lithium is introduced into the anode, the anode must be protected from moisture and oxygen in subsequent manufacturing steps.
[0011] Another problem arises when the method for manufacturing the battery includes annealing of the electrodes (which is usually the case in the case of all-solid-state batteries without a liquid phase): such annealing can lead to lithium losses, which are detrimental to the operation of the battery. In some cases, annealing can also lead to the formation of parasitic products. For example, when using a battery made of Li4Ti5O 12 When the anode is made, trace amounts of TiO2-type impurities may appear in the electrode, depending on the heat treatment conditions used. The phases formed by these impurities can interfere with the operation of the battery because the lithium insertion potential of these phases (1.55 V) is different from that of Li4Ti5O 12 The lithium insertion potential is 1.7 V.
[0012] Furthermore, it has been observed that certain electrolyte materials, such as, for example, amorphous polyethylene oxide, can irreversibly intercalate with lithium during the first charge process.
[0013] Another problem is that the anode becomes sensitive to contact with the atmosphere after the initial charge is completed. In view of so many difficulties, it is preferable to avoid these conditions rather than compensate for the consequences.
[0014] The present invention aims to propose a method for manufacturing a microbattery with electrodes and a more stable electrolyte. More specifically, it is desirable to overcome the irreversible capacity loss of the electrodes and / or certain solid electrolyte films covering the electrodes. It is also desirable to obtain an anode that does not show any significant irreversible loss during the first charge. Summary of the invention
[0015] Purpose of the Invention
[0016] According to the invention, the problem can be solved by using a protective coating on the anode, which protects the anode from the influence of the ambient atmosphere, in particular from the influence of oxygen, carbon dioxide and moisture. The protective coating can be applied to the anode film and / or the powder particles of the anode material. The protective coating is preferably deposited by an atomic layer deposition technique known as ALD (acronym, Atomic Layer Deposition). The thickness of the protective coating is preferably less than 5 nm. The ALD technique can form dense layers without holes and with extremely thin thickness; these coatings are very dense. The coating can be made of Li3PO4 or aluminum oxide in particular. The protective coating can be covered with a solid electrolyte membrane, for example a LLZO layer deposited from nanoparticles.
[0017] The present invention may be implemented on any type of anode that can be used in a lithium ion battery.
[0018] In a first embodiment, the anode may be a dense anode, such as an all-solid-state anode, which is deposited by electrophoresis of monodisperse nanoparticles contained in a suspension, as described in patent application WO 2013 / 064773, or the anode is deposited by vapor deposition. In this case, the anode is covered with a protective coating before the anode is embedded with lithium and before the battery is assembled. The protective coating may have a very thin thickness and may be formed by atomic layer deposition ALD, or chemically formed in solution by a method known as CSD (acronym, Chemical Solution Dissolution). For example, an electronic insulator may be used, in particular an oxide such as silicon oxide, aluminum oxide or zirconium oxide; the thickness of such a coating preferably does not exceed 2nm to 3nm. However, the density level of such a coating for the atmosphere depends on its thickness, and it is advantageous to further deposit a dense solid electrolyte that is also resistant to the atmosphere, thereby improving the protection of the anode after the anode is embedded with lithium and before the battery is assembled. The dense solid electrolyte coating may be deposited by ALD, or chemically by solution CSD, wherever feasible, or by any other suitable technique for complex stoichiometric ratios. The thin layer of electronic insulator deposited by ALD or chemically by solution CSD also limits side reactions at the interface between the solid electrolyte coating and the anode.
[0019] In a second embodiment, the anode may be a porous anode, preferably a mesoporous anode, having a network of nanoparticles interconnected by ion-conducting paths, while retaining pores, preferably mesopores; these pores may be filled with a liquid ion conductor, for example an ionic liquid containing a dissolved lithium salt. According to the invention, the porous anode, preferably a mesoporous anode, is protected by a dense coating before being pre-embedded with lithium, wherein the dense coating is deposited by ALD or chemically deposited by solution CSD. Advantageously, the coating is an electronic insulator, in particular an oxide such as silicon oxide, aluminum oxide or zirconium oxide, but a solid electrolyte layer may also be deposited.
[0020] The present invention may be implemented in any type of lithium-ion battery.
[0021] In any case, by using this coating, the anode can be pre-intercalated with lithium without having to worry about the lithium reacting with air or moisture during the cell assembly steps, or even less during use of the cell.
[0022] The first object of the present invention is to provide an anode for a lithium ion battery, which comprises at least one anode material and does not contain a binder, wherein the anode is pre-embedded with lithium ions, and is characterized in that the anode material deposited on a conductive substrate that can be used as an anode collector is covered with a protective coating, which is in contact with the anode material, and the protective coating can protect the anode material from the influence of the ambient atmosphere.
[0023] The anode according to the present invention may be a porous anode, preferably a mesoporous anode.
[0024] The anode can be produced by a chemical vapor deposition technique, in particular by a physical vapor deposition technique such as sputtering and / or by a chemical vapor deposition technique, wherein the chemical vapor deposition technique may be plasma-assisted.
[0025] Alternatively, the anode may be made from a suspension of nanoparticles of at least one anode material by electrophoretic deposition techniques, or by immersion. Advantageously, the suspension of nanoparticles (i.e., colloidal suspension) may contain nanoparticles of at least one anode material having a primary diameter D50 less than or equal to 50 nm.
[0026] Alternatively, the colloidal suspension may comprise aggregates of nanoparticles of the anode material. Advantageously, the protective coating comprises a first layer in contact with the anode material, the first layer being deposited chemically by the ALD technique (atomic layer deposition) or by solution CSD, the thickness of the first layer being less than 10 nm, preferably less than 5 nm, even more preferably between 1 nm and 3 nm. Advantageously, the first layer is an electron insulator oxide, preferably selected from the group consisting of silicon oxide, aluminum oxide and zirconium oxide. Advantageously, the protective coating comprises a second layer deposited on the first layer, the second layer being made of a material selected from the group consisting of:
[0027] Phosphates, such as Li3PO4, LiPO3, (Li3Al 0.4 Sc 1.6 (PO4)3、Li 1.2 Zr 1.9 Ca 0.1 (PO4)3; LiZr2(PO4)3; Li 1+3x Zr2(P 1-x Si x O4)3, of which 1.8 <x<2.3;Li 1+6x Zr2(P 1-x B x O4)3, where 0≤x≤0.25; Li3(Sc 2-x M x )(PO4)3, where M = Al or Y and 0≤x≤1; Li1+x M x (Sc) 2-x (PO4)3, where M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1-y Sc y ) 2-x (PO4)3, wherein 0≤x≤0.8; 0≤y≤1 and M=Al or Y or a mixture of these two compounds; Li 1+x M x (Ga) 2-x (PO4)3, where M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li 1+x Al x Ti 2-x (PO4)3, where 0≤x≤1, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li 1+x Al x Ge 2-x (PO4)3, where 0≤x≤1; or Li 1+x+z M x (Ge 1-y Ti y ) 2-x Si z P 3-z O 12 , wherein 0≤x≤0.8 and 0≤y≤1.0&0≤z≤0.6, and M=Al, Ga or Y, or a mixture of two or three of these compounds; Li 3+y (Sc 2-x M x )Q y P 3-y O 12 , wherein M = Al and / or Y and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y M x Sc 2-x Q y P 3-y O 12 , wherein M = Al, Y, Ga or a mixture of these three compounds, and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y+z M x (Ga 1-y Sc y ) 2-x Q z P3-z O 12 , where 0≤x≤0.8; 0≤y≤1; 0≤z≤0.6, where M=Al or Y or a mixture of these two compounds, and Q=Si and / or Se; or Li 1+ x Zr 2-x B x (PO4)3, where 0≤x≤0.25; or Li 1+x Zr 2-x Ca x (PO4)3, where 0≤x≤0.25; or Li 1+x N x M 2- x P3O 12 , where 0≤x≤1 and N=Cr, V, Ca, B, Mg, Bi and / or Mo, M=Sc, Sn, Zr, Hf, Se or Si, or a mixture of these compounds;
[0028] Borates, such as Li3BO3, LiBO2, Li3(Sc 2-x M x )(BO3)3, where M = Al or Y and 0≤x≤1; Li 1+x M x (Sc) 2-x (BO3)3, where 0≤x≤0.8 and M=Al, Y, Ga or a mixture of these three compounds; Li 1+x M x (Ga 1- y Sc y ) 2-x (BO3)3, where 0≤x≤0.8, 0≤y≤1 and M=Al or Y; Li 1+x M x (Ga) 2-x (BO3)3, where M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li3BO3-Li2SO4, Li3BO3-Li2SiO4, Li3BO3-Li2SiO4-Li2SO4;
[0029] Silicates, such as Li2SiO3, Li2Si5O 11 , Li2Si2O5, Li2SiO6, LiAlSiO4, Li4SiO4, LiAlSi2O6;
[0030] Oxides, such as Al2O3, LiNbO3 coatings;
[0031] · Fluorides, such as AlF3, LaF3, CaF2, LiF, CeF3;
[0032] · Anti - perovskite compounds, selected from: Li3OA, where A is a halogen element or a mixed halogen element, preferably at least one element selected from F, Cl, Br, I, or a mixture of two, three, or four of these elements; Li (3-x) M x / 2 OA, where 0 < x ≤ 3, M is a divalent metal, preferably at least one element selected from the elements Mg, Ca, Ba, Sr, or a mixture of two, three, or four of these elements, and A is a halogen element or a mixed halogen element, preferably at least one element selected from the elements F, Cl, Br, I, or a mixture of two, three, or four of these elements; Li (3-x) M 3 x / 3 OA, where 0 ≤ x ≤ 3, M 3 is a trivalent metal, A is a halogen element or a mixed halogen element, preferably at least one element selected from the elements F, Cl, Br, I, or a mixture of two, three, or four of these elements; or LiCOX z Y (1-z) , where X and Y are halogen elements such as those listed above for A, and 0 ≤ z ≤ 1,
[0033] · Mixtures of different components included in the group.
[0034] A second object of the present invention is a method for manufacturing an anode for a lithium - ion battery according to the present invention, comprising the following steps:
[0035] (a) Depositing an anode material on the substrate;
[0036] (b) Depositing a protective coating on the anode material;
[0037] (c) Polarizing the anode material in a solution containing lithium cations so that the anode material is embedded with lithium ions.
[0038] In this method, the deposition of the anode material can be carried out by vapor deposition techniques, in particular by physical vapor deposition techniques (such as cathodic sputtering) and / or by chemical vapor deposition techniques (which can be plasma - assisted). Alternatively, the deposition of the anode material can be carried out by electrophoresis from a suspension of nanoparticles of at least one anode material, or by immersion.
[0039] A final object of the invention is a lithium-ion battery comprising an anode according to the invention, or an anode obtainable by a process according to the invention, and also comprising an electrolyte in contact with said anode and a cathode in contact with said electrolyte.
[0040] The electrolyte is a conductor of lithium ions and is advantageously selected from the group consisting of:
[0041] - all-solid-state electrolytes deposited by vapor deposition,
[0042] - electrophoretically deposited all-solid-state electrolytes,
[0043] an electrolyte formed by a separator impregnated with a liquid electrolyte, generally an aprotic solvent comprising a lithium salt or an ionic liquid comprising one or more lithium salts, or a mixture of such an aprotic solvent and an ionic liquid,
[0044] a porous electrolyte, preferably a mesoporous electrolyte, impregnated with a liquid electrolyte, typically an aprotic solvent comprising a lithium salt or an ionic liquid comprising one or more lithium salts, or a mixture of such an aprotic solvent and an ionic liquid,
[0045] - an electrolyte comprising a polymer impregnated with a liquid electrolyte and / or a lithium salt,
[0046] - An electrolyte formed from a lithium-ion conducting solid electrolyte material, such as, preferably, an oxide, a sulfide or a phosphate.
[0047] The cathode may in particular be an all-solid cathode or a porous cathode, preferably a mesoporous cathode.The cathode may carry a protective coating of the same type as the protective coating of the anode. DETAILED DESCRIPTION
[0048] 1. definition
[0049] The capacity (mAh) of a battery or cell is the current (mA) that can be drawn from the cell in 1 hour. This shows how long the battery can last.
[0050] In the present context, particle size is defined by its largest dimension. "Nanoparticle" refers to any particle or object having nanometer dimensions, at least one dimension of which is less than or equal to 100 nm.
[0051] "Suspension" refers to any liquid in which solid particles are dispersed. In the context of this article, the terms "suspension of nanoparticles" and "colloidal suspension" are used interchangeably. "Suspension of nanoparticles" or "colloidal suspension" refers to any liquid in which solid particles are dispersed.
[0052] "Mesoporous material" refers to any solid having pores in its structure called "mesopores", wherein the size of the pores is between the size of micropores (width less than 2nm) and the size of macropores (width greater than 50nm), i.e. the size of the pores is 2nm to 50nm. This term corresponds to the terminology adopted by IUPAC (International Union of Pure and Applied Chemistry), which is a reference for those skilled in the art. Therefore, the term "nanopore" is not used herein, although in terms of the definition of nanoparticles, mesopores as defined above have nanometer dimensions, and it is known that those skilled in the art refer to pores whose size is smaller than the size of mesopores as "micropores".
[0053] An introduction to the concept of porosity (and the term disclosed above) is given in the article “Texture of matériaux pulverulents ou poreux” by F. Rouquerol et al., published in the collection “Techniques de l'Ingénieur” (traitéAnalyseet Caractérisation, fascicule P 1050); the article also describes techniques for characterizing porosity, in particular the BET method.
[0054] For the purposes of the present invention, "mesoporous electrode" or "mesoporous layer" refers to a layer or electrode having mesopores. As will be explained below, in these electrodes or layers, these mesopores contribute significantly to the total pore volume; the expression "mesoporous electrode / layer having a mesoporosity greater than X volume %" used in the description below is used to refer to this state.
[0055] According to the definition of IUPAC (which is a reference for those skilled in the art), "aggregate" refers to a weakly connected collection of primary particles. Herein, these primary particles are nanoparticles, and the diameter of the nanoparticles can be determined by transmission electron microscopy. The aggregates of the primary nanoparticles that are aggregated can usually be destroyed (i.e., reduced to primary nanoparticles) in a suspension of the liquid phase under ultrasound according to techniques known to those skilled in the art.
[0056] 2. summary
[0057] The invention is applied to batteries with dense electrodes or porous electrodes, preferably mesoporous electrodes. Dense electrodes can be deposited electrophoretically from suspensions containing non-aggregated primary nanoparticles (monodisperse particles), i.e. the diameter of the particles in the suspension corresponds to their primary diameter. The particle size of the anode material is a key parameter for depositing dense electrodes by electrophoresis, since the residual porosity of the layer decreases after the morphological reorganization of the nanoparticles during their thermal and / or mechanical compaction; the driving forces for this reorganization are the surface energy and the energy associated with the structural defects.
[0058] In order to obtain a dense anode, it is advantageous if the primary diameter D of the particles is 50 Less than 100 nm, preferably less than 50 nm, even more preferably less than 30 nm. The primary diameter herein refers to the diameter of non-aggregated particles. The same diameter limitation is advantageous for the deposition of dense layers of cathode materials and electrolytes constituting the battery. The absolute value of the zeta potential of these primary nanoparticle suspensions is generally greater than 50 mV, preferably greater than 60 mV. These suspensions can be prepared in different ways, for example, directly prepared by hydrothermal synthesis of anode material nanoparticles; in order to obtain a stable suspension, it is necessary to purify it to reduce (or even remove) its ionic charge.
[0059] According to the invention, the deposition of the anode layer used can also be carried out by vapor deposition techniques, in particular by physical vapor deposition or by chemical vapor deposition, or by a combination of these two techniques. Vapor deposition techniques can produce dense layers in particular.
[0060] A porous electrode, preferably a mesoporous electrode, can be electrophoretically deposited from a suspension comprising aggregates of primary nanoparticles.
[0061] When the porous layer is deposited by electrophoretic deposition, the primary particles are at least partially aggregated in the suspension used. Advantageously, the size of these aggregates is 80nm to 300nm, preferably 100nm to 200nm. Such suspensions with at least partially aggregated nanoparticles can be prepared directly by hydrothermal synthesis of the primary nanoparticles: these suspensions are stable only when purified (i.e., without their residual ionic charge). Therefore, a suspension of at least partially aggregated nanoparticles can be obtained by partially purifying the suspension obtained by hydrothermal synthesis. Alternatively, a purified suspension can be used and the suspension can be made unstable by adding ions (e.g., lithium salts, such as LiOH). The absolute value of the zeta potential of such a suspension is generally less than 50mV, preferably less than 45mV.
[0062] According to the invention, the layers in the battery, in particular the anode, are free of binders. The electrode layers are generally deposited on a substrate capable of serving as current collector; in a known manner, metal or polymer foils coated with a conductive layer made of metal or oxide can be used.
[0063] According to the invention, the anode can be made in particular from an anode material selected from:
[0064] -Carbon nanotubes, graphene, graphite;
[0065] -Lithium iron phosphate, the typical molecular formula is LiFePO4;
[0066] -Mixed silicon tin oxynitride, typical molecular formula is Si a Snb O y N z , where a > 0, b > 0, a + b ≤ 2, 0 < y ≤ 4, 0 < z ≤ 3, also known as SiTON, especially SiSn 0.87 O 1.2 N 1.72 ;
[0067] - Carbonitride oxides, with a typical molecular formula of Si a Sn b C c O y N z , where a > 0, b > 0, a + b ≤ 2, 0 < c < 10, 0 < y < 24, 0 < z < 17;
[0068] - Si x N y type nitrides (especially x = 3 and y = 4), Sn x N y type nitrides (especially x = 3 and y = 4), Zn x N y type nitrides (especially x = 3 and y = 2), Li 3-x M x N type nitrides (where when M = Co, 0 ≤ x ≤ 0.5; when M = Ni, 0 ≤ x ≤ 0.6; when M = Cu, 0 ≤ x ≤ 0.3); Si 3-x M x N4 type nitrides, where 0 ≤ x ≤ 3.
[0069] - Oxides SnO2, SnO, Li2SnO3, SnSiO3, Li x SiO y (x >= 0 and 2 > y > 0), Li4Ti5O 12 , TiNb2O7, Co3O4, SnB 0.6 P 0.4 O 2.9 and TiO2,
[0070] - Composite oxide TiNb2O7, which contains 0 wt% to 10 wt% of carbon, preferably, the carbon is selected from graphene and carbon nanotubes.
[0071] The morphology and structure of the anode layer depend on its deposition technique, and a person skilled in the art will be able to distinguish, for example, between a dense layer deposited by electrophoresis, a dense layer deposited by vapor deposition, and a porous or mesoporous layer deposited by electrophoresis. For example, the density of the so-called dense electrode layer deposited by electrophoresis according to the technique described in patent document WO 2013 / 064773 is at least 80%, preferably at least 90%, even more preferably at least 95% of the theoretical density of the solid substance. On the other hand, the layers deposited by vapor deposition are generally very uniform, free of pores, and may have a columnar growth. The porous layer, preferably the mesoporous layer, deposited by electrophoresis has a specific morphology, characterized by a network of pores, preferably a network of mesopores, present in transmission electron microscopy.
[0072] The conductive substrate useful as current collector may be a metal, such as a metal foil, or a polymer foil or a metallized non-metal (ie coated with a metal layer). The substrate is preferably selected from foils made of titanium, copper, nickel or stainless steel.
[0073] The metal foil may be coated with a layer of a noble metal, in particular a noble metal selected from gold, platinum, titanium or an alloy mainly comprising at least one or more of these metals, or with a layer of an ITO type conductive material (which also has the function of a diffusion barrier).
[0074] By using solid materials, in particular foils made of titanium, copper or nickel, the cut edges of the electrodes in the battery can also be protected from corrosion.
[0075] Stainless steel can also be used as current collector, especially when the stainless steel contains titanium or aluminum as alloying elements or when the surface of the stainless steel has a thin layer of protective oxide.
[0076] Other substrates that can be used as current collectors are, for example, semi-noble metals covered with a protective coating, thereby preventing any dissolution of these foils due to the presence of an electrolyte in contact with them.
[0077] These semi-precious metal foils may be foils made of copper, nickel, or foils made of metal alloys, such as foils made of stainless steel, foils made of Fe-Ni alloy, Be-Ni-Cr alloy, Ni-Cr alloy, or Ni-Ti alloy.
[0078] The coating that can be used to protect the substrate used as a current collector can be of different natures. The coating can be:
[0079] • A thin layer obtained by a sol-gel process of the same material as the electrode material. The absence of pores in the film prevents contact between the electrolyte and the metal current collector.
[0080] - Thin layers obtained by vacuum deposition, in particular by physical vapor deposition (PVD) or chemical vapor deposition (CVD), of the same material as the electrode material.
[0081] Dense and defect-free thin metal layers, for example of gold, titanium, platinum, palladium, tungsten or molybdenum. These metals can be used to protect the current collector, since they have good electrical conductivity and can withstand the heat treatment in the subsequent method of manufacturing the electrode. The layer can be produced in particular by electrochemical methods, PVD, CVD, evaporation, ALD.
[0082] - A thin layer of carbon, such as diamond carbon, graphite, deposited by ALD, PVD, CVD, or by inking from a sol-gel solution, which makes it possible, after a heat treatment, to obtain an inorganic phase doped with carbon to make it conductive.
[0083] A coating capable of protecting a substrate used as a current collector must be electrically conductive in order to avoid impairing the operation of an electrode subsequently deposited on the coating by giving the electrode an excessively high resistance.
[0084] Usually, in order not to affect the operation of the battery too much, the maximum dissolution current (in μA / cm 2 The surface capacity of the electrode (in μAh / cm 2 indicates) is 1000 times smaller.
[0085] 3. Anodic layer treatment after anodic layer deposition
[0086] Layers deposited by electrophoresis require specific treatment after their deposition. First, they must be dried after they have been removed from contact with the suspension from which they were deposited. Drying must not cause the formation of cracks. Drying is therefore preferably carried out under controlled humidity and temperature conditions. The drying step of the anode material layer is preferably carried out after the electrophoretic deposition is completed and before the deposition of the protective coating begins.
[0087] The drying step of the anodic layer may be carried out at atmospheric pressure, preferably at a temperature of 30 to 120° C. Drying under pressure reduces the risk of weakening the layer due to violent detachment of liquid evaporating from subsurface areas of the layer.
[0088] Due to the size of the particles and their melting temperature, the drying step may be limited to the removal of the liquid phase of the suspension, or it may carry out the consolidation of the layer. Furthermore, depending on the nature of the materials forming these layers, their crystalline state, their particle size, the anodic layer may be subjected to an optional annealing after drying, which may be preceded and / or accompanied by pressing. This is necessary in order to optimize the electrochemical properties of the anodic film.
[0089] Heat treating the deposited anode material to form a porous anode is described in the "Alternative Method" section below.
[0090] 4. Anodic layer protection
[0091] Before the anode layer is pre-embedded, a protective coating (also referred to as a protective coating) is deposited. For layers deposited by electrophoresis, the protective coating is deposited after drying and / or consolidation. The purpose of the protective coating is to protect the pre-embedded anode from the atmosphere to prevent lithium from leaving the anode in contact with the atmosphere. Before the battery is assembled, the protective coating is applied to the anode. The protective coating acts as a protective layer. The protective coating prevents the formation of secondary products that reduce the embedding capacity of lithium cations. The protective coating also prevents the anode from losing lithium ions that have been embedded in the anode structure.
[0092] The protective coating must be dense and strong. In an advantageous embodiment, the protective coating is deposited chemically by ALD or by solution CSD. These deposition techniques by ALD or by CSD allow encapsulation coating that can truly reproduce the topography of the substrate; encapsulation coating can be performed along the entire surface of the electrode.
[0093] Advantageously, the thickness of the protective coating is less than 10 nm and advantageously greater than 2 nm to ensure a good barrier effect. The coatings obtained by ALD or CSD are very protective even at thin thicknesses, since they are free of holes ("pinholes") and are therefore dense. Moreover, these coatings are thin enough not to alter the properties of the anode. For dense layers (free of holes), the water vapor transmission rate (WVTP) decreases as the thickness of the layer increases.
[0094] Advantageously, the deposition of the protective coating comprises depositing a layer of electrically insulating material by ALD or by CSD, the electrically insulating material preferably being selected from aluminium oxide, silicon oxide or zirconium oxide, or being selected from lithium ion conductive solid electrolyte materials, preferably Li3PO4, the thickness of the protective coating being 1 nm to 5 nm, preferably 1 nm to 4 nm, more preferably 1 nm to 3 nm.
[0095] For example, the anode may be covered with a dense and strong protective membrane in contact with the atmosphere, the protective membrane being made of a stable ion-conducting material.
[0096] The protective film can be:
[0097] o Phosphate coatings, for example, coatings of the following phosphates: Li3PO4, LiPO3, (Li3Al 0.4 Sc 1.6 (PO4)3、Li 1.2Zr 1.9 Ca 0.1 (PO4)3; LiZr2(PO4)3; Li 1+3x Zr2(P 1-x Si x O4)3, of which 1.8 <x<2.3;Li 1+6x Zr2(P 1- x B x O4)3, where 0≤x≤0.25; Li3(Sc 2-x M x )(PO4)3, where M = Al or Y and 0≤x≤1; Li 1+x M x (Sc) 2-x (PO4)3, where M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1-y Sc y ) 2-x (PO4)3, wherein 0≤x≤0.8; 0≤y≤1 and M=Al or Y or a mixture of these two compounds; Li 1+x M x (Ga) 2-x (PO4)3, where M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li 1+x Al x Ti 2-x (PO4)3, where 0≤x≤1, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li 1+x Al x Ge 2-x (PO4)3, where 0≤x≤1; or Li 1+x+z M x (Ge 1- y Ti y ) 2-x Si z P 3-z O 12 , wherein 0≤x≤0.8 and 0≤y≤1.0&0≤z≤0.6, and M=Al, Ga or Y, or a mixture of two or three of these compounds; Li 3+y (Sc 2-x M x )Q y P 3-y O 12, wherein M = Al and / or Y and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y M x Sc 2-x Q y P 3-y O 12 , wherein M = Al, Y, Ga or a mixture of these three compounds, and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y+z M x (Ga 1- y Sc y ) 2-x Q z P 3-z O 12 , where 0≤x≤0.8; 0≤y≤1; 0≤z≤0.6, where M=Al or Y or a mixture of these two compounds, and Q=Si and / or Se; or Li 1+x Zr 2-x B x (PO4)3, where 0≤x≤0.25; or Li 1+x Zr 2-x Ca x (PO4)3, where 0≤x≤0.25; or Li 1+x N x M 2-x P3O 12 , where 0≤x≤1 and N=Cr, V, Ca, B, Mg, Bi and / or Mo, M=Sc, Sn, Zr, Hf, Se or Si, or a mixture of these compounds;
[0098] o Borate coatings, for example, coatings of the following borates: Li3BO3, LiBO2, Li3(Sc 2-x M x )(BO3)3, where M = Al or Y and 0≤x≤1; Li 1+x M x (Sc) 2-x (BO3)3, where 0≤x≤0.8 and M=Al, Y, Ga or a mixture of these three compounds; Li 1+x M x (Ga 1-y Sc y ) 2-x (BO3)3, where 0≤x≤0.8, 0≤y≤1 and M=Al or Y; Li 1+x M x (Ga) 2-x(BO3)3, where M = Al, Y, or a mixture of these two compounds, and 0 ≤ x ≤ 0.8; Li3BO3-Li2SO4, Li3BO3-Li2SiO4, Li3BO3-Li2SiO4-Li2SO4;
[0099] ○ Silicate coatings, for example, coatings of the following silicates: Li2SiO3, Li2Si5O 11 , Li2Si2O5, Li2SiO6, LiAlSiO4, Li4SiO4, LiAlSi2O6;
[0100] ○ Oxide coatings, for example, coatings of Al2O3, LiNbO3;
[0101] ○ Fluoride coatings, for example, coatings of AlF3, LaF3, CaF2, LiF, CeF3;
[0102] ○ Coatings of perovskite-type compounds, where the perovskite-type compounds are selected from: Li3OA, where A is a halogen element or a mixed halogen element, preferably at least one element selected from F, Cl, Br, I, or a mixture of two, three, or four of these elements; Li (3-x) M x / 2 OA, where 0 < x ≤ 3, M is a divalent metal, preferably at least one element selected from the elements Mg, Ca, Ba, Sr, or a mixture of two, three, or four of these elements, and A is a halogen element or a mixed halogen element, preferably at least one element selected from the elements F, Cl, Br, I, or a mixture of two, three, or four of these elements; Li (3-x) M 3 x / 3 OA, where 0 ≤ x ≤ 3, M 3 is a trivalent metal, and A is a halogen element or a mixed halogen element, preferably at least one element selected from the elements F, Cl, Br, I, or a mixture of two, three, or four of these elements; or LiCOX z Y (1-z) , where X and Y are halogen elements as listed above for A, and 0 ≤ z ≤ 1;
[0103] ○ Coatings composed of a mixture of different前述 components.
[0104] The protective film can also be made of an electron insulator type oxide material. For example, oxides of the aluminum oxide (Al2O3), silicon oxide or zirconium oxide type can be deposited, especially if the thickness is low, especially a thickness of less than about 5 nm, preferably 2 nm to 3 nm. The barrier effect of these layers deposited by ALD increases with the thickness of the layer, but since the ALD technique is slow, it is desirable to deposit as thin a layer as possible. For porous anode layers, preferably mesoporous anode layers, a protective coating can be deposited by ALD or by CSD, preferably by ALD; the thickness of the protective coating does not exceed 5 nm. For porous anode layers, preferably mesoporous anode layers, it is advantageous to deposit a protective coating by ALD, especially within the pores of the porous anode layer. This technology can coat the interior of the pores, especially pores of small size, i.e. pores with a diameter of several nanometers.
[0105] As explained above, in order to deposit a thicker protective coating, in particular with a thickness greater than 5 nm, on the anode, in particular a dense anode, it is advantageous to use a lithium ion conducting material, so that a dense electrolyte coating is deposited from nanoparticles. This electrolyte coating can be deposited on a first thin coating deposited by ALD or by CSD, which can be an electronic insulator; this embodiment prevents the electrolyte material from reacting with the anode material. The stable solid electrolyte that can be subsequently deposited from nanoparticles as a protective coating and in contact with the atmosphere can be those coatings previously listed as dense and strong protective films to cover the anode, and can be selected from the group consisting of: lithium phosphates, lithium borates, lithium silicates, lithium oxides, lithium-rich antiperovskites, mixtures of these components.
[0106] Even more preferably, the protective coating comprises at least one compound selected from the group consisting of:
[0107] ○ Garnet, preferably selected from: Li7La3Zr2O 12 ;Li6La2BaTa2O 12 ;Li 5.5 LqCy 1.75 In 0.25 O 12 ;Li5La3M2O 12 , where M = Nb or Ta or a mixture of these two compounds; Li 7-x Ba x La 3-x M2O 12 , where 0≤x≤1, and M=Nb or Ta or a mixture of these two compounds; Li 7-x Ln3Z 2-x M x O 12, wherein 0≤x≤2, and M=Al, Ga or Ta or a mixture of two or three of these compounds;
[0108] ○ Lithium phosphate, preferably selected from: Li3PO4; LiPO3; Li3Al 0.4 Sc 1.6 (PO4)3, the acronym is LASP, Li 1.2 Zr 1.9 Ca 0.1 (PO4)3; LiZr2(PO4)3; Li 1+3x Zr2(P 1-x Si x O4)3, of which 1.8 <x<2.3;Li 1+6x Zr2(P 1- x B x O4)3, where 0≤x≤0.25; Li3(Sc 2-x M x )(PO4)3, where M = Al or Y, and 0≤x≤1; Li 1+x M x (Sc) 2-x (PO4)3, where M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1-y Sc y ) 2-x (PO4)3, wherein 0≤x≤0.8; 0≤y≤1 and M=Al or Y or a mixture of these two compounds; Li 1+x M x (Ga) 2-x (PO4)3, wherein M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li 1+x Al x Ti 2-x (PO4)3, where 0≤x≤1, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li 1+x Al x Ge 2-x (PO4)3, where 0≤x≤1; or Li 1+x+z M x (Ge 1-y Ti y ) 2- x Si z P 3-z O 12, wherein 0≤x≤0.8 and 0≤y≤1.0&0≤z≤0.6, and M=Al, Ga or Y, or a mixture of two or three of these compounds; Li 3+y (Sc 2-x M x )Q y P 3-y O 12 , wherein M = Al and / or Y, and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y M x Sc 2-x Q y P 3-y O 12 , where M = Al, Y, Ga or a mixture of these three compounds, and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y+z M x (Ga 1-y Sc y ) 2- x Q z P 3-z O 12 , wherein 0≤x≤0.8; 0≤y≤1; 0≤z≤0.6, wherein M=Al or Y or a mixture of these two compounds, and Q=Si and / or Se; or Li 1+x Zr 2-x B x (PO4)3, where 0≤x≤0.25; or Li 1+x Zr 2-x Ca x (PO4)3, where 0≤x≤0.25; or Li 1+x N x M 2-x P3O 12 , where 0≤x≤1 and N=Cr, V, Ca, B, Mg, Bi and / or Mo, M=Sc, Sn, Zr, Hf, Se or Si, or a mixture of these compounds;
[0109] ○ Lithium borate, preferably selected from: Li3(Sc 2-x M x )(BO3)3, where M = Al or Y, and 0≤x≤1; Li 1+x M x (Sc) 2-x (BO3)3, wherein M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1-y Sc y ) 2-x (BO3)3, where 0 ≤ x ≤ 0.8; 0 ≤ y ≤ 1 and M = Al or Y; Li 1+x M x (Ga) 2-x (BO3)3, where M = Al, Y or a mixture of these two compounds, and 0 ≤ x ≤ 0.8; Li3BO3, LiBO2, Li3BO3-Li2SO4, Li3BO3-Li2SiO4, Li3BO3-Li2SiO4-Li2SO4;
[0110] ○ Nitrogen oxides, preferably selected from Li3PO 4-x N 2x / 3 、Li4SiO 4-x N 2x / 3 、Li4GeO 4-x N 2x / 3 , where 0 < x < 4 or Li3BO 3-x N 2x / 3 , where 0 < x < 3;
[0111] ○ Lithium compounds based on lithium and phosphorus nitrogen oxides (referred to as LiPON), which are in the form of Li x PO y N z , where x ~ 2.8, 2y + 3z ~ 7.8 and 0.16 ≤ z ≤ 0.4, especially Li 2.9 PO 3.3 N 0.46 , and can also be the compound Li w PO x N y S z , where 2x + 3y + 2z = 5 = w, or the compound Li w PO x N y S z , where 3.2 ≤ x ≤ 3.8, 0.13 ≤ y ≤ 0.4, 0 ≤ z ≤ 0.2, 2.9 ≤ w ≤ 3.3, or Li t P x Al y O u N v S w compounds of the form, where 5x + 3y = 5, 2u + 3v + 2w = 5 + t, 2.9 ≤ t ≤ 3.3, 0.84 ≤ x ≤ 0.94, 0.094 ≤ y ≤ 0.26, 3.2 ≤ u ≤ 3.8, 0.13 ≤ v ≤ 0.46, 0 ≤ w ≤ 0.2;
[0112] ○ Materials based on lithium phosphorus or lithium boron nitrides (referred to as LiPON and LIBON), which can also contain silicon, sulfur, zirconium, aluminum, or a combination of aluminum, boron, sulfur, and / or silicon, and for materials based on lithium phosphorus nitride, boron can be included;
[0113] ○ Lithium compounds based on lithium, phosphorus, and silicon nitride, called LiSiPON, especially Li 1.9 Si 0.28 P 1.0 O 1.1 N 1.0 ;
[0114] ○ Lithium nitrides of the LiBON, LiBSO, LiSiPON, LiSON, thio-LiSiCON, LiPONB types (where B, P, and S represent boron, phosphorus, and sulfur, respectively);
[0115] ○ Lithium oxides, preferably selected from Li7La3Zr2O 12 or Li 5+x La3(Zr x ,A 2-x )O 12 , where A = Sc, Y, Al, Ga and 1.4 ≤ x ≤ 2, or Li 0.35 La 0.55 TiO3 or Li 3x La 2 / 3-x TiO3, where 0 ≤ x ≤ 0.16;
[0116] ○ Silicates, preferably selected from Li2Si2O5, Li2SiO3, Li2SiO6, Li2Si2O6, LiAlSiO4, Li4SiO4, LiAlSi2O6, Li2Si5O 11 ;
[0117] ○ Perovskite - type solid electrolytes, selected from: Li3OA, where A is a halogen element or a mixed halogen element, preferably at least one element selected from F, Cl, Br, I, or a mixture of two, three, or four of these elements; Li (3-x) M x / 2 OA, where 0 < x ≤ 3, M is a divalent metal, preferably at least one element selected from the elements Mg, Ca, Ba, Sr, or a mixture of two, three, or four of these elements, and A is a halogen element or a mixed halogen element, preferably at least one element selected from the elements F, Cl, Br, I, or a mixture of two, three, or four of these elements; Li (3-x) M 3 x / 3OA, where 0 ≤ x ≤ 3, M 3is a trivalent metal, A is a halogen element or a mixed halogen element, preferably at least one element selected from the group consisting of F, Cl, Br, and I, or a mixture of two, three, or four of these elements; or LiCOX z Y (1-z) , wherein X and Y are halogen elements such as those listed above for A, and 0≤z≤1;
[0118] ○Compound La 0.51 Li 0.34 Ti 2.94 , Li 3.4 V 0.4 Ge 0.6 O4, Li2O-Nb2O5, LiAlGaSPO4;
[0119] ○Based on Li2CO3, B2O3, Li2O, Al(PO3)3LiF, P2S3, Li2S, Li3N, Li 14 Zn(GeO4)4、Li 3.6 Ge 0.6 V 0.4 O4, LiTi2(PO4)3, Li 3.25 Ge 0.25 P 0.25 S4, Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1+x Al x M 2-x (PO4)3 (wherein M = Ge, Ti and / or Hf, and where 0 <x<1)、Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (wherein 0≤x≤1 and 0≤y≤1), a formulation of LiNbO3.
[0120] 5. Anode pre-embedding
[0121] After covering the anode with this protective coating (in the case of a dense anode, the protective coating can be a coating deposited by ALD or by CSD, which can be covered by a dense electrolyte membrane; and in the case of a porous anode, the protective coating can be a coating deposited by ALD or by CSD), the anode can be lithium-intercalated by immersing it in a liquid electrolyte and polarizing it. Several charge and discharge cycles can be performed to achieve a fully reversible behavior of the anode. The lithium-intercalated anode can then be assembled with the cathode by hot pressing without risk of losing lithium: the solid electrolyte layer covering the anode prevents the mobile lithium from leaving the anode.
[0122] Depending on the purpose to be achieved, several situations may occur regarding the step of inserting lithium ions into the anode. The pre-insertion method according to the invention may be carried out in order to offset the irreversible losses during the first charge. In this case, the pre-insertion is carried out in such a way that lithium is inserted into the anode at a potential from the initial potential of the anode to the potential of the anode at the end of lithium insertion, and then a new scan is carried out until the initial potential is returned to allow the mobile lithium to leave. The new reversible capacity of the anode that has undergone pre-insertion is less than the reversible capacity during the first charge. This capacity value of the anode that has undergone pre-insertion will reach a balance with the capacity of the cathode. This embodiment is particularly applicable to anodes based on nitrides and nitrogen oxides; this makes it possible to increase the specific energy of the battery element.
[0123] The pre-embedding method according to the present invention can also be performed to optimize the operating voltage range of the battery, thereby ensuring excellent performance in cycling and offsetting the Li4Ti5O-based 12 In fact, according to the manufacturing mode, Li4Ti5O 12 Thermal treatment of the nanoparticles allows the formation of oxides in the form of TiO2 or adjacent to their surface. These oxides will intercalate lithium at 1.7V instead of Li4Ti5O 12 The lithium insertion potential is 1.55V. The voltage of the cell is the potential difference between the cathode and the anode. In order to ensure that the cathode is always in its reversibility range during its operation, it is important to be able to accurately relate the voltage of the cell to the potential of the cathode. Therefore, it is useful that the anode is always operated at only 1.55V. The potential of the cathode is then 1.55V minus the voltage of the cell. It is important to 12 The anode is pre-embedded to cross the plateau to 1.7 V, and the anode is at 1.55 V before assembly. The reversible capacity of the anode at 1.55 V must be slightly higher than the reversible capacity of the cathode.
[0124] The electrodes, which are preferably coated with a protective layer (e.g., a protective layer made of a ceramic oxide or a solid electrolyte), are charged by polarization in a solution containing lithium cations. After charging, these electrodes can be operated in a full cell in an optimized voltage range without irreversible losses occurring during the first charge.
[0125] 6. Battery Manufacturing
[0126] The protected pre-intercalated anodes according to the present invention are suitable for any type of electrolyte suitable for lithium-ion batteries.
[0127] Advantageously, the electrolyte of the battery consists of the following materials:
[0128] a separator impregnated with a liquid electrolyte, typically an aprotic solvent comprising a lithium salt or an ionic liquid comprising one or more lithium salts, or a mixture of such an aprotic solvent and an ionic liquid,
[0129] a porous insulator structure, preferably a mesoporous insulator structure, impregnated with a liquid electrolyte, typically an aprotic solvent comprising a lithium salt or an ionic liquid comprising one or more lithium salts, or a mixture of such an aprotic solvent and an ionic liquid,
[0130] - polymers impregnated with liquid electrolytes and / or lithium salts, or
[0131] - Lithium-ion conducting solid electrolyte materials (eg oxides, sulfides, phosphates).
[0132] Advantageously, when the electrolyte of the battery consists of a polymer impregnated with a lithium salt, the polymer is preferably selected from the group consisting of polyethylene oxide, polyimide, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polysiloxane, and the lithium salt is preferably selected from the group consisting of LiCl, LiBr, LiI, Li(ClO4), Li(BF4), Li(PF6), Li(AsF6), Li(CH3CO2), Li(CF3SO3), Li(CF3SO2)2N, Li(CF3SO2)3, Li(CF3CO2), Li(B(C6H5)4), Li(SCN), Li(NO3).
[0133] Advantageously, the ionic liquid may be 1-ethyl-3-methylimidazolium (also known as EMI + ) and / or N-propyl-N-methylpyrrolidinium (also known as PYR 13 + ) and / or N-butyl-N-methylpyrrolidinium (also known as PYR 14 + ) type cations and bis(trifluoromethylsulfonyl)imide (TFSI- ) and / or bis(fluorosulfonyl)imide (FSI - ) type anions are associated. In order to form an electrolyte, a lithium salt of the LiTFSI type can be dissolved in an ionic liquid used as a solvent, or in a solvent such as γ-butyrolactone. γ-Butyrolactone can prevent the crystallization of the ionic liquid, especially the crystallization of the ionic liquid at low temperatures, wherein the crystallization of the ionic liquid leads to a higher operating temperature range. Advantageously, when the porous anode or cathode comprises lithium phosphate, the phase carrying lithium ions may comprise a solid electrolyte, such as LiBH4, or a mixture of LiBH4 and one or more compounds selected from LiCl, LiI and LiBr. LiBH4 is a good conductor of lithium and has a low melting point, and LiBH4 facilitates its impregnation in the porous electrode, especially by immersion. Due to its extremely high reducibility, LiBH4 is rarely used as an electrolyte. By using a protective film on the surface of the porous lithium phosphate electrode, the reduction of the electrode material, especially the cathode material, by LiBH4 is prevented, thereby preventing the degradation of the electrode.
[0134] Advantageously, the phase loaded with lithium ions comprises at least one ionic liquid, preferably at least one room temperature ionic liquid, such as PYR14TFSI, which is dilutable in at least one solvent, such as gamma-butyrolactone.
[0135] Advantageously, the phase loaded with lithium ions comprises from 10% to 40% by weight of solvent, preferably from 30% to 40% by weight of solvent, even more preferably from 30% to 40% by weight of gamma-butyrolactone.
[0136] Advantageously, the phase loaded with lithium ions comprises more than 50% by weight of at least one ionic liquid and less than 50% by weight of solvent, which reduces the safety risk and the risk of fire in the event of a malfunction of a battery comprising such a phase loaded with lithium ions.
[0137] Advantageously, the lithium ion-carrying phase comprises:
[0138] - 30 to 40% by weight of a solvent, preferably 30 to 40% by weight of gamma-butyrolactone, and
[0139] - more than 50% by weight of at least one ionic liquid, preferably more than 50% by weight of PYR14TFSI.
[0140] The phase loaded with lithium ions may be an electrolyte comprising PYR14TFSI, LiTFSI and γ-butyrolactone, preferably an electrolyte comprising about 90 wt % of PYR14TFSI, 0.7 M of LiTFSI, and 10 wt % of γ-butyrolactone.
[0141] Advantageously, the electrolyte material layer is made of a solid electrolyte material selected from the following materials:
[0142] ○With formula Li d A 1 x A 2 y (TO4) z of garnet, among which
[0143] ■A 1 represents a cation in the +II oxidation state, preferably Ca, Mg, Sr, Ba, Fe, Mn, Zn, Y, Gd; and wherein
[0144] ■A 2 represents a cation in the +III oxidation state, preferably Al, Fe, Cr, Ga, Ti, La; and wherein
[0145] ■ (TO4) represents an anion in which T is an atom in the +IV oxidation state, which is located at the center of the tetrahedron formed by the oxygen atoms, and in which TO4 advantageously represents a silicate or zirconate anion, it being known that all or part of the element T in the +IV oxidation state may be replaced by atoms in the +III or +V oxidation state, such as Al, Fe, As, V, Nb, In, Ta;
[0146] ■ It is known that: d is 2 to 10, preferably 3 to 9, even more preferably 4 to 8; x is 3, but may be 2.6 to 3.4 (preferably 2.8 to 3.2); y is 2, but may be 1.7 to 2.3 (preferably 1.9 to 2.1), and z is 3, but may be 2.9 to 3.1;
[0147] ○ Garnet, preferably selected from: Li7La3Zr2O 12 ;Li6La2BaTa2O 12 ;Li 5.5 LqCy 1.75 In 0.25 O 12 ;Li5La3M2O 12 , where M = Nb or Ta or a mixture of these two compounds; Li 7-x Ba x La 3-x M2O 12 , where 0≤x≤1, and M=Nb or Ta or a mixture of these two compounds; Li 7-x Ln3Z 2-x M x O 12 , wherein 0≤x≤2, and M=Al, Ga or Ta or a mixture of two or three of these compounds;
[0148] ○ Lithium phosphate, preferably selected from: NaSICON type lithium phosphate, Li3PO4; LiPO3; Li3Al 0.4 Sc 1.6 (PO4)3, the abbreviation of which is LASP, Li 1.2 Zr 1.9 Ca 0.1 (PO4)3; LiZr2(PO4)3; Li 1+3x Zr2(P 1-x Si x O4)3, of which 1.8 <x<2.3;Li 1+6x Zr2(P 1-x B x O4)3, where 0≤x≤0.25; Li3(Sc 2-x M x )(PO4)3, where M = Al or Y, and 0≤x≤1; Li 1+x M x (Sc) 2-x (PO4)3, where M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1-y Sc y ) 2-x (PO4)3, wherein 0≤x≤0.8; 0≤y≤1, and M=Al or Y or a mixture of these two compounds; Li 1+x M x (Ga) 2-x (PO4)3, wherein M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li 1+x Al x Ti 2-x (PO4)3, where 0≤x≤1, is abbreviated as LATP, or Li 1+x Al x Ge 2-x (PO4)3, where 0≤x≤1, its acronym is LAGP; or Li 1+x+z M x (Ge 1-y Ti y ) 2-x Si z P 3-z O 12 , wherein 0≤x≤0.8, 0≤y≤1.0 and 0≤z≤0.6, and M=Al, Ga or Y or a mixture of two or three of these compounds; Li 3+y (Sc 2-x Mx )Q y P 3-y O 12 , wherein M=Al and / or Y and Q=Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y M x Sc 2- x Q y P 3-y O 12 , wherein M = Al, Y, Ga or a mixture of these three compounds, and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y+z M x (Ga 1-y Sc y ) 2-x Q z P 3-z O 12 , wherein 0≤x≤0.8; 0≤y≤1; 0≤z≤0.6, wherein M=Al or Y or a mixture of these two compounds, and Q=Si and / or Se; or Li 1+x Zr 2-x B x (PO4)3, where 0≤x≤0.25; or Li 1+x Zr 2-x Ca x (PO4)3, where 0≤x≤0.25; or Li 1+x N x M 2-x P3O 12 , wherein 0≤x≤1, and N=Cr, V, Ca, B, Mg, Bi and / or Mo, M=Sc, Sn, Zr, Hf, Se or Si or a mixture of these compounds;
[0149] ○ Lithium borate, preferably selected from: Li3(Sc 2-x M x )(BO3)3, where M = Al or Y, and 0≤x≤1; Li 1+x M x (Sc) 2-x (BO3)3, wherein M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1- y Sc y ) 2-x (BO3)3, wherein 0≤x≤0.8; 0≤y≤1, and M=Al or Y; Li 1+xM x (Ga) 2-x (BO3)3, where M = Al, Y or a mixture of these two compounds, and 0 ≤ x ≤ 0.8; Li3BO3, Li3BO3 - Li2SO4, Li3BO3 - Li2SiO4, Li3BO3 - Li2SiO4 - Li2SO4;
[0150] ○ Nitrogen oxides, preferably selected from Li3PO 4-x N 2x / 3 、Li4SiO 4-x N 2x / 3 、Li4GeO 4-x N 2x / 3 , where 0 < x < 4, or Li3BO 3-x N 2x / 3 , where 0 < x < 3;
[0151] ○ Lithium compounds based on lithium phosphorus nitrogen oxides (referred to as LiPON), which are in the form of Li x PO y N z , where x ~ 2.8, 2y + 3z ~ 7.8 and 0.16 ≤ z ≤ 0.4, especially Li 2.9 PO 3.3 N 0.46 , and can also be the compound Li w PO x N y S z in the form of, where 2x + 3y + 2z = 5 = w, or is the compound Li w PO x N y S z in the form of, where 3.2 ≤ x ≤ 3.8, 0.13 ≤ y ≤ 0.4, 0 ≤ z ≤ 0.2, 2.9 ≤ w ≤ 3.3, or is Li t P x Al y O u N v S w in the form of a compound, where 5x + 3y = 5, 2u + 3v + 2w = 5 + t, 2.9 ≤ t ≤ 3.3, 0.84 ≤ x ≤ 0.94, 0.094 ≤ y ≤ 0.26, 3.2 ≤ u ≤ 3.8, 0.13 ≤ v ≤ 0.46, 0 ≤ w ≤ 0.2;
[0152] ○ Nitrogen oxides based on lithium phosphorus or lithium boron (referred to as LiPON and LIBON), which can also contain silicon, sulfur, zirconium, aluminum, or a combination of aluminum, boron, sulfur, and / or silicon, and for materials based on lithium phosphorus nitrogen oxides, boron can be included;
[0153] ○ Lithium compounds based on lithium, phosphorus and silicon oxynitride, known as LiSiPON, especially Li 1.9 Si 0.28 P 1.0 O 1.1 N 1.0 ;
[0154] ○ Lithium oxynitrides of the LiBON, LiBSO, LiSiPON, LiSON, thio-LiSiCON, LiPONB type (where B, P and S represent boron, phosphorus and sulfur respectively);
[0155] ○ Lithium oxides, preferably selected from Li7La3Zr2O 12 or Li 5+x La3(Zr x , A 2-x )O 12 , where A = Sc, Y, Al, Ga and 1.4 ≤ x ≤ 2, or Li 0.35 La 0.55 TiO3 or Li 3x La 2 / 3-x TiO3, where 0 ≤ x ≤ 0.16 (LLTO);
[0156] ○ Silicates, preferably selected from Li2Si2O5, Li2SiO3, Li2Si2O6, LiAlSiO4, Li4SiO4, LiAlSi2O6;
[0157] ○ Perovskite-type solid electrolytes, selected from: Li3OA, where A is a halogen element or a mixed halogen element, preferably at least one element selected from F, Cl, Br, I, or a mixture of two, three or four of these elements; Li (3-x) M x / 2 OA, where 0 < x ≤ 3, M is a divalent metal, preferably at least one element selected from the elements Mg, Ca, Ba, Sr, or a mixture of two, three or four of these elements, A is a halogen element or a mixed halogen element, preferably at least one element selected from the elements F, Cl, Br, I, or a mixture of two, three or four of these elements; Li (3-x) M 3 x / 3OA, where 0 ≤ x ≤ 3, M 3 is a trivalent metal, A is a halogen element or a mixed halogen element, preferably at least one element selected from the elements F, Cl, Br, I, or a mixture of two, three or four of these elements; or LiCOX z Y (1-z) , where X and Y are halogen elements such as those listed above for A, and 0 ≤ z ≤ 1;
[0158] ○Compound La 0.51 Li 0.34 Ti 2.94 , Li 3.4 V 0.4 Ge 0.6 O4, Li2O-Nb2O5, LiAlGaSPO4;
[0159] ○Based on Li2CO3, B2O3, Li2O, Al(PO3)3LiF, P2S3, Li2S, Li3N, Li 14 Zn(GeO4)4、Li 3.6 Ge 0.6 V 0.4 O4, LiTi2(PO4)3, Li 3.25 Ge 0.25 P 0.25 S4, Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1+x Al x M 2-x (PO4)3 (wherein M = Ge, Ti and / or Hf, and where 0 <x<1)、Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (wherein 0≤x≤1 and 0≤y≤1).
[0160] Regarding the morphology of the electrolyte layer, different types of lithium ion conducting electrolyte layers can be used in the context of the present invention. Dense layers can be used, as is known from patent document WO 2013 / 064 772. Porous layers can also be used, preferably mesoporous layers, which can be impregnated with polymers or ionic liquids containing lithium ions; this will be described in detail below.
[0161] The cathode of the battery according to the present invention may be formed of a cathode material selected from the following materials:
[0162] -Oxide: LiMn2O4; Li 1+x Mn 2-x O4, where 0 <x<0.15;LiCoO2;LiNiO2;LiMn 1.5 Ni 0.5 O4; LiMn 1.5 Ni 0.5-x X xO4, wherein X is selected from Al, Fe, Cr, Co, Rh, Nd, rare earth elements such as Sc, Y, Lu, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and wherein 0 <x<0.1;LiMn 2-x M x O4, wherein M = Er, Dy, Gd, Tb, Yb, Al, Y, Ni, Co, Ti, Sn, As, Mg or a mixture of these compounds, and wherein 0 <x<0.4;LiFeO2;LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O2; LiAl x Mn 2-x O4, where 0≤x<0.15; LiNi 1 / x Co 1 / y Mn 1 / z O2, where x+y+z=10;
[0163] - Phosphates LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3; phosphates of the chemical formula LiMM'PO4, wherein M and M' (M≠M') are selected from Fe, Mn, Ni, Co, V;
[0164] - All lithium forms the following chalcogenides: V2O5, V3O8, TiS2, titanium oxysulfide (TiO y S z , where z = 2-y and 0.3≤y≤1), tungsten oxysulfide (WO y S z , where z=2-y and 0.3≤y≤1), CuS, CuS2.
[0165] 7. Variations of the Invention
[0166] The present invention can be implemented with porous anodes and / or cathodes, preferably with mesoporous anodes and / or cathodes. Advantageously, the thickness of the thin layer porous electrode deposited on the substrate is less than 10 μm, preferably less than 8 μm, and even more preferably from 1 μm to 6 μm. The porous electrode does not contain a binder. The porous electrode has pores with an average diameter of less than 100 nm, preferably less than 80 nm. Advantageously, the porosity of the porous electrode is greater than 30% by volume, preferably from 30% to 55% by volume, more preferably from 35% to 50% by volume, and even more preferably from 40% to 50% by volume.
[0167] A porous anode or cathode, preferably a mesoporous anode or cathode, may be produced by the following method, wherein:
[0168] (A) Providing a colloidal suspension comprising an average primary diameter D 50 Aggregates or agglomerates of nanoparticles of at least one material P less than or equal to 50 nm (preferably 10 nm to 30 nm), the average diameter of the aggregates or agglomerates being 80 nm to 300 nm (preferably 100 nm to 200 nm),
[0169] (B) immersing the substrate together with the counter electrode in the colloidal suspension provided in step (A),
[0170] (C) applying a voltage between said substrate and said counter electrode to obtain electrophoretic deposition of an electrode layer on said substrate, wherein the electrode layer comprises aggregates of nanoparticles of said at least one material P,
[0171] (D) drying the layer, preferably under a stream of air,
[0172] It is known that steps (B), (C) and (D) can be repeated.
[0173] The material P is an anode material for manufacturing a porous anode, or a cathode material for manufacturing a porous cathode.
[0174] In an alternative embodiment, the method comprises the steps of:
[0175] (A1) providing a colloidal suspension comprising a primary diameter D 50 Nanoparticles of at least one material P with a size of 50 nm or less;
[0176] (A2) destabilizing the nanoparticles present in the colloidal suspension to form clusters of particles having an average diameter of 80 nm to 300 nm, preferably 100 nm to 200 nm, preferably by adding a destabilizing agent such as a salt, wherein the salt is preferably LiOH;
[0177] (B) immersing the substrate together with the counter electrode in the colloidal suspension containing aggregates or agglomerates of nanoparticles obtained in step (A2);
[0178] (C) applying a voltage between said substrate and said counter electrode to obtain electrophoretic deposition of an electrode layer on said substrate, wherein the electrode layer comprises aggregates of nanoparticles of said at least one material P,
[0179] (D) drying the layer, preferably under a stream of air,
[0180] In order to obtain a porous electrode layer by this method, the layer obtained at the end of step (D) must be subjected to a specific treatment. The dried layer can be consolidated by pressing and / or heating steps. In a very advantageous embodiment of the invention, the treatment causes partial coalescence of the primary nanoparticles in the aggregates and between adjacent aggregates; this phenomenon is called "necking" or "neck formation". It is characterized by partial coalescence of two particles in contact, the particles remain separated, but are connected by a neck (contraction). Lithium ions can migrate within these necks and can diffuse from one particle to another without encountering particle boundaries. As a result, the three-dimensional network composed of interconnected particles has strong ion mobility and conductivity; the network includes pores, preferably mesopores. The temperature required to obtain "necking" depends on the material; taking into account the diffusion nature that causes the "necking" phenomenon, the duration of the treatment depends on the temperature.
[0181] The average diameter of the pores is from 2 nm to 80 nm, preferably from 2 nm to 50 nm, preferably from 6 nm to 30 nm, even more preferably from 8 nm to 20 nm.
[0182] According to this alternative, during the deposition of the protective coating on the porous anode by ALD or by CSD, the protective coating is deposited on and within the pores of the porous anode material. The total thickness of the protective coating of the porous anode should not exceed 10 nm, preferably kept below 5 nm, so as not to block the pores.
[0183] For the first layer of the protective coating, preferably an electrically insulating material is selected, which may in particular be aluminum oxide, silicon oxide or zirconium oxide, or a lithium-ion-conducting solid electrolyte of Li3PO4; the thickness of the first layer is advantageously 1 nm to 5 nm, preferably 2 nm to 4 nm. Advantageously, if a second layer is subsequently deposited, the thickness of the first layer of the protective coating is 1 nm to 3 nm. Advantageously, after the deposition of the layer of electrically insulating material or the layer of the solid electrolyte by ALD or by CSD, a second thin layer of at least one solid electrolyte is deposited from a suspension by immersion or electrophoresis, wherein the suspension contains monodisperse nanoparticles of at least one solid electrolyte material.
[0184] The second layer of the protective coating may be a solid electrolyte material selected from the group consisting of:
[0185] ● Phosphates, such as Li3PO4, LiPO3, (Li3Al 0.4 Sc 1.6 (PO4)3、Li 1.2 Zr 1.9 Ca 0.1 (PO4)3; LiZr2(PO4)3; Li 1+3x Zr2(P1-x Si x O4)3, of which 1.8 <x<2.3;Li 1+6x Zr2(P 1-x B x O4)3, where 0≤x≤0.25; Li3(Sc 2-x M x )(PO4)3, where M = Al or Y and 0≤x≤1; Li 1+x M x (Sc) 2-x (PO4)3, where M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1-y Sc y ) 2-x (PO4)3, wherein 0≤x≤0.8; 0≤y≤1 and M=Al or Y or a mixture of these two compounds; Li 1+x M x (Ga) 2-x (PO4)3, where M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li 1+x Al x Ti 2-x (PO4)3, where 0≤x≤1, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li 1+x Al x Ge 2-x (PO4)3, where 0≤x≤1; or Li 1+x+z M x (Ge 1-y Ti y ) 2-x Si z P 3-z O 12 , wherein 0≤x≤0.8 and 0≤y≤1.0&0≤z≤0.6, and M=Al, Ga or Y, or a mixture of two or three of these compounds; Li 3+y (Sc 2-x M x )Q y P 3-y O 12 , wherein M = Al and / or Y and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y M x Sc 2-x Q y P3-y O 12 , wherein M = Al, Y, Ga or a mixture of these three compounds, and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y+z M x (Ga 1-y Sc y ) 2-x Q z P 3-z O 12 , where 0≤x≤0.8; 0≤y≤1; 0≤z≤0.6, where M=Al or Y or a mixture of these two compounds, and Q=Si and / or Se; or Li 1+ x Zr 2-x B x (PO4)3, where 0≤x≤0.25; or Li 1+x Zr 2-x Ca x (PO4)3, where 0≤x≤0.25; or Li 1+x N x M 2- x P3O 12 , where 0≤x≤1 and N=Cr, V, Ca, B, Mg, Bi and / or Mo, M=Sc, Sn, Zr, Hf, Se or Si, or a mixture of these compounds;
[0186] ●Borate, such as Li3BO3, LiBO2, Li3(Sc 2-x M x )(BO3)3, where M = Al or Y and 0≤x≤1; Li 1+x M x (Sc) 2-x (BO3)3, where 0≤x≤0.8 and M=Al, Y, Ga or a mixture of these three compounds; Li 1+x M x (Ga 1-y Sc y ) 2-x (BO3)3, where 0≤x≤0.8, 0≤y≤1 and M=Al or Y; Li 1+x M x (Ga) 2-x (BO3)3, where M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li3BO3-Li2SO4, Li3BO3-Li2SiO4, Li3BO3-Li2SiO4-Li2SO4;
[0187] ● Silicates, such as Li2SiO3, Li2Si5O 11 , Li2Si2O5, Li2SiO6, LiAlSiO4, Li4SiO4, LiAlSi2O6;
[0188] ● Oxides, such as Al2O3, LiNbO3 coatings;
[0189] ● Fluorides, such as AlF3, LaF3, CaF2, LiF, CeF3;
[0190] ● Anti - perovskite compounds selected from: Li3OA, where A is a halogen element or a mixed halogen element, preferably at least one element selected from F, Cl, Br, I, or a mixture of two, three, or four of these elements; Li (3-x) M x / 2 OA, where 0 < x ≤ 3, M is a divalent metal, preferably at least one element selected from the elements Mg, Ca, Ba, Sr, or a mixture of two, three, or four of these elements, A is a halogen element or a mixed halogen element, preferably at least one element selected from the elements F, Cl, Br, I, or a mixture of two, three, or four of these elements; Li (3-x) M 3 x / 3 OA, where 0 ≤ x ≤ 3, M 3 is a trivalent metal, A is a halogen element or a mixed halogen element, preferably at least one element selected from the elements F, Cl, Br, I, or a mixture of two, three, or four of these elements; or LiCOX z Y (1 -z), where X and Y are halogen elements such as those listed above for A, and 0 ≤ z ≤ 1,
[0191] ● Mixtures of different components included in the group.
[0192] Advantageously, the porous electrode is impregnated with an electrolyte, which is preferably an ionic liquid containing a lithium salt; the ionic liquid can be diluted with an aprotic solvent.
[0193] In another alternative of the present invention, the cathode material is also covered with a protective coating; the same method as for protecting the anode material can be used. More precisely, the cathode material is covered with a protective coating in contact with the cathode material, where the cathode material is deposited on a conductive substrate that can be used as a cathode current collector, and the protective coating can protect the cathode material from the influence of the ambient atmosphere.
[0194] Examples
[0195] The following examples illustrate certain aspects of the present invention, but these examples do not limit the scope of the present invention.
[0196] Example 1 :Manufacturing of pre-embedded anodes
[0197] By converting Li4Ti5O 12 The powder was ground / dispersed in anhydrous ethanol at about 10 g / L and a few ppm of citric acid was added to prepare a suspension of the anode material. The grinding was performed to obtain a particle size D 50 Stable suspension of less than 70nm.
[0198] By making the Li4Ti5O contained in the suspension 12 The nanoparticles are electrophoresed to deposit an anodic layer; an anodic layer having a thickness of 1 μm is deposited on both sides of the first substrate; the anodic layer is dried and heat-treated at a temperature of about 600° C. The anodic layer is a so-called “dense” layer which has undergone a thermal consolidation step to increase the density of the layer.
[0199] A protective coating of 10 nm thick Li3PO4 was then deposited by ALD to cover the anode. The ceramic electrolyte Li3Al 0.4 Sc 1.6 A (PO4)3 (abbreviated LASP) layer is deposited on the anode layer; the thickness of the LASP layer is about 500 nm. The electrolyte layer is then dried and consolidated by heat treatment at about 600°C.
[0200] The anode was then immersed in a LiPF6 / EC / DMC solution, the counter electrode was made of metallic lithium, and charged to 1.55 V. The capacity of the anode at its reversible platform of 1.55 V was greater than that of the cathode.
[0201] Example 2 : Fabrication of batteries including pre-embedded anodes
[0202] A suspension containing about 10 g / L of cathode material was prepared by grinding / dispersing LiMn2O4 powder in water. 0.4 Sc 1.6 (PO4)3 was ground / dispersed in anhydrous ethanol to prepare a suspension containing 5 g / L of ceramic electrolyte material. The grinding was performed to obtain a particle size D 50 Stable suspension of particles smaller than 50 nm.
[0203] The cathode was prepared by electrophoretically depositing LiMn2O4 nanoparticles contained in the above suspension in the form of a thin film deposited on both sides of the second substrate; the cathode layer having a thickness of 1 μm was then heat-treated at about 600°C.
[0204] The anode and cathode obtained in Example 1 were then stacked on their electrolyte faces, and the whole was kept at 500° C. under pressure for 15 minutes; thereby a lithium-ion battery capable of many charge and discharge cycles was obtained.
Claims
1. An anode for a lithium ion battery, comprising at least one anode material and no binder, wherein the anode is pre-embedded with lithium ions, characterized in that: The anode is a porous anode, and the anode material deposited on a conductive substrate capable of serving as an anode current collector is covered by a protective coating in contact with the anode material, the protective coating being capable of protecting the anode material from the ambient atmosphere.
2. The anode according to claim 1, characterized in that The anode material is selected from the group consisting of: -Carbon nanotubes, graphene, graphite; -Lithium iron phosphate, the typical molecular formula is LiFePO4; - Mixed silicon tin oxynitride, with a typical molecular formula of Si a Sn b O y N z , where a > 0, b > 0, a + b ≤ 2, 0 < y ≤ 4, 0 < z ≤ 3, also known as SiTON; -Carbon and nitrogen oxides, the typical molecular formula is Si a Sn b C c O y N z , where a>0, b>0, a+b≤2,0 <c<10,0<y<24,0<z<17; -Si x N y Type nitride; Sn x N y Type nitride; Zn x N y Type nitride; Li 3-x M x N-type nitride, wherein when M=Co, 0≤x≤0.5, when M=Ni, 0≤x≤0.6, and when M=Cu, 0≤x≤0.3; or Si 3-x M x N4 type nitride, where 0≤x≤3; - oxides SnO2, SnO, Li2SnO3, SnSiO3, Li with x>=0 and 2>y>0 x SiO y 、Li4Ti5O 12 、TiNb2O7、Co3O4、SnB 0.6 P 0.4 O 2.9 and TiO2, - A complex oxide TiNb2O7 containing 0 to 10% by weight of carbon.
3. The anode according to claim 1, characterized in that The anode is a mesoporous anode.
4. The anode according to claim 1, characterized in that The protective coating comprises a first layer, the first layer being in contact with the anode material, the first layer having a thickness of less than 10 nm.
5. The anode according to claim 4, characterized in that The first layer is an electronic insulator oxide.
6. The anode according to claim 5, characterized in that The electronic insulator oxide is selected from the group consisting of silicon oxide, aluminum oxide, and zirconium oxide.
7. The anode according to claim 4, characterized in that The protective coating comprises a second layer deposited on the first layer, the second layer being made of a material selected from the group consisting of: Phosphates; Borates; Silicates; Oxides; Fluoride; ·Perovskite - type compounds, selected from: Li3OA, where A is a halogen element or a mixed halogen element; Li (3-x) M x / 2 OA, where 0 < x ≤ 3, M is a divalent metal, and A is a halogen element or a mixed halogen element; Li (3-x) M 3 x / 3 OA, where 0 ≤ x ≤ 3, M 3 is a trivalent metal, and A is a halogen element or a mixed halogen element; or LiCOX z Y (1-z) , where X and Y are halogen elements, and 0 ≤ z ≤ 1, • Mixtures of the different components contained in the group.
8. The anode according to claim 7, characterized in that The second layer of the protective coating is selected from the group consisting of: Phosphate selected from: Li3PO4, LiPO3, Li3Al 0.4 Sc 1.6 (PO4)3、Li 1.2 Zr 1.9 Ca 0.1 (PO4)3; LiZr2(PO4)3; Li 1+3x Zr2(P 1-x Si x O4)3, of which 1.8 <x<2.3;Li 1+6x Zr2(P 1-x B x O4)3, where 0≤x≤0.25; Li3(Sc 2-x M x )(PO4)3, where M = Al or Y and 0≤x≤1; Li 1+x M x (Sc) 2-x (PO4)3, where M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1-y Sc y ) 2-x (PO4)3, wherein 0≤x≤0.8; 0≤y≤1 and M=Al or Y or a mixture of these two compounds; Li 1+x M x (Ga) 2-x (PO4)3, where M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li 1+x Al x Ti 2-x (PO4)3, where 0≤x≤1, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li 1+ x Al x Ge 2-x (PO4)3, where 0≤x≤1; or Li 1+x+z M x (Ge 1-y Ti y ) 2-x Si z P 3-z O 12 , wherein 0≤x≤0.8 and 0≤y≤1.0&0≤z≤0.6, and M=Al, Ga or Y, or a mixture of two or three of these compounds; Li 3+y (Sc 2-x M x )Q y P 3-y O 12 , wherein M = Al and / or Y and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y M x Sc 2-x Q y P 3-y O 12 , wherein M = Al, Y, Ga or a mixture of these three compounds, and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y+z M x (Ga 1-y Sc y ) 2-x Q z P 3-z O 12 , where 0≤x≤0.8; 0≤y≤1; 0≤z≤0.6, where M=Al or Y or a mixture of these two compounds, and Q=Si and / or Se; or Li 1+x Zr 2-x B x (PO4)3, where 0≤x≤0.25; or Li 1+x Zr 2-x Ca x (PO4)3, where 0≤x≤0.25; or Li 1+x N x M 2-x P3O 12 , where 0≤x≤1 and N=Cr, V, Ca, B, Mg, Bi and / or Mo, M=Sc, Sn, Zr, Hf, Se or Si, or a mixture of these compounds; Borates selected from Li3BO3, LiBO2, Li3(Sc 2-x M x )(BO3)3, where M = Al or Y and 0≤x≤1; Li 1+x M x (Sc) 2-x (BO3)3, where 0≤x≤0.8 and M=Al, Y, Ga or a mixture of these three compounds; Li 1+x M x (Ga 1- y Sc y ) 2-x (BO3)3, where 0≤x≤0.8, 0≤y≤1 and M=Al or Y; Li 1+x M x (Ga) 2-x (BO3)3, where M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li3BO3-Li2SO4, Li3BO3-Li2SiO4, Li3BO3-Li2SiO4-Li2SO4; Silicate, selected from Li2SiO3, Li2Si5O 11 , Li2Si2O5, Li2SiO6, LiAlSiO4, Li4SiO4, LiAlSi2O6; Oxide selected from Al2O3, LiNbO3 coating; Fluoride selected from AlF3, LaF3, CaF2, LiF, CeF3; · Anti-perovskite compound Li (3-x) M x / 2 OA, where 0 < x ≤ 3, M is a divalent metal, which is at least one element among Mg, Ca, Ba, Sr, or a mixture of two, three, or four of these elements, and A is a halogen element or a mixed halogen element.
9. The anode according to claim 1, characterized in that The protective coating comprises at least one compound selected from the group consisting of: ○ Garnet; ○Lithium phosphate; ○Lithium borate; ○Nitrogen oxides; ○ Lithium compounds based on lithium phosphorus nitride oxide, which are Li x PO y N z In the form of, wherein x = 2.8, 2y + 3z = 7.8 and 0.16 ≤ z ≤ 0.4, the compound Li w PO x N y S z In the form of 2x+3y+2z=5=w, it is a compound Li w PO x N y S z In the form of, 3.2≤x≤3.8, 0.13≤y≤0.4, 0≤z≤0.2, 2.9≤w≤3.3, or Li t P x Al y O u N v S w Compounds of the form wherein 5x+3y=5, 2u+3v+2w=5+t, 2.9≤t≤3.3, 0.84≤x≤0.94, 0.094≤y≤0.26, 3.2≤u≤3.8, 0.13≤v≤0.46, 0≤w≤0.2; ○ Materials based on lithium phosphorus or lithium boron nitride oxide, known as LiPON and LIBON; ○ Lithium compounds based on lithium, phosphorus and silicon oxynitride, known as LiSiPON; ○Lithium oxynitrides of the type LiBSO, LiSON, sulfo-LiSiCON, and LiPONB, wherein B, P, and S represent boron, phosphorus, and sulfur, respectively; ○Lithium oxide; ○ Silicates; ○Inverse perovskite solid electrolyte, selected from: Li3OA, where A is a halogen element or a mixed halogen element; Li (3-x) M x / 2 OA, where 0 < x ≤ 3, M is a divalent metal, and A is a halogen element or a mixed halogen element; Li (3-x) M 3 x / 3 OA, where 0 ≤ x ≤ 3, M 3 is a trivalent metal, and A is a halogen element or a mixed halogen element; or LiCOX z Y (1-z) , where X and Y are halogen elements, and 0 ≤ z ≤ 1; ○ Compound La 0.51 Li 0.34 Ti 2.94 、Li 3.4 V 0.4 Ge 0.6 O4, Li2O-Nb2O5, LiAlGaSPO4; ○Based on Li2CO3, B2O3, Li2O, Al(PO3)3LiF, P2S3, Li2S, Li3N, Li 14 Zn(GeO4)4、Li 3.6 Ge 0.6 V 0.4 O4, LiTi2(PO4)3, Li 3.25 Ge 0.25 P 0.25 S4, Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1+x Al x M 2-x (PO4)3, wherein M = Ge, Ti and / or Hf, and wherein 0 <x<1、Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 , wherein 0≤x≤1 and 0≤y≤1, a formulation of LiNbO3.
10. The anode according to claim 9, characterized in that The protective coating comprises at least one compound selected from the group consisting of: ○Garnet, selected from: Li7La3Zr2O 12 ;Li6La2BaTa2O 12 ;Li 5.5 LqCy 1.75 In 0.25 O 12 ;Li5La3M2O 12 , where M = Nb or Ta or a mixture of these two compounds; Li 7-x Ba x La 3-x M2O 12 , where 0≤x≤1, and M=Nb or Ta or a mixture of these two compounds; Li 7-x Ln3Z 2-x M x O 12 , wherein 0≤x≤2, and M=Al, Ga or Ta or a mixture of two or three of these compounds; ○Lithium phosphate, selected from: Li3PO 4; LiPO3; Li3Al 0.4 Sc 1.6 (PO4)3, the acronym is LASP, Li 1.2 Zr 1.9 Ca 0.1 (PO4)3; LiZr2(PO4)3; Li 1+3x Zr2(P 1-x Si x O4)3, of which 1.8 <x<2.3;Li 1+6x Zr2(P 1-x B x O4)3, where 0≤x≤0.25; Li3(Sc 2-x M x )(PO4)3, where M = Al or Y, and 0≤x≤1; Li 1+x M x (Sc) 2-x (PO4)3, where M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1-y Sc y ) 2-x (PO4)3, wherein 0≤x≤0.8; 0≤y≤1 and M=Al or Y or a mixture of these two compounds; Li 1+x M x (Ga) 2-x (PO4)3, wherein M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li 1+x Al x Ti 2-x (PO4)3, where 0≤x≤1, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li 1+x Al x Ge 2-x (PO4)3, where 0≤x≤1; or Li 1+x+z M x (Ge 1-y Ti y ) 2-x Si z P 3-z O 12 , wherein 0≤x≤0.8 and 0≤y≤1.0&0≤z≤0.6, and M=Al, Ga or Y, or a mixture of two or three of these compounds; Li 3+y (Sc 2-x M x )Q y P 3-y O 12 , wherein M = Al and / or Y, and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y M x Sc 2-x Q y P 3-y O 12 , wherein M = Al, Y, Ga or a mixture of these three compounds, and Q = Si and / or Se, 0≤x≤0.8 and 0≤y≤1; or Li 1+x+y+z M x (Ga 1-y Sc y ) 2-x Q z P 3-z O 12 , wherein 0≤x≤0.8; 0≤y≤1; 0≤z≤0.6, wherein M=Al or Y or a mixture of these two compounds, and Q=Si and / or Se; or Li 1+ x Zr 2-x B x (PO4)3, where 0≤x≤0.25; or Li 1+x Zr 2-x Ca x (PO4)3, where 0≤x≤0.25; or Li 1+x N x M 2- x P3O 12 , wherein 0≤x≤1 and N=Cr, V, Ca, B, Mg, Bi and / or Mo, M=Sc, Sn, Zr, Hf, Se or Si, or a mixture of these compounds; ○ Lithium borate selected from: Li3(Sc 2-x M x )(BO3)3, where M = Al or Y, and 0≤x≤1; Li 1+x M x (Sc) 2-x (BO3)3, wherein M = Al, Y, Ga or a mixture of these three compounds, and 0≤x≤0.8; Li 1+x M x (Ga 1-y Sc y ) 2-x (BO3)3, where 0≤x≤0.8; 0≤y≤1 and M=Al or Y; Li 1+x M x (Ga) 2-x (BO3)3, wherein M = Al, Y or a mixture of these two compounds, and 0≤x≤0.8; Li3BO3, LiBO2, Li3BO3-Li2SO4, Li3BO3-Li2SiO4, Li3BO3-Li2SiO4-Li2SO4; ○ Nitrogen oxides, selected from Li3PO 4-x N 2x / 3 、Li4SiO 4-x N 2x / 3 、Li4GeO 4-x N 2x / 3 , where 0 < x < 4 or Li3BO 3-x N 2x / 3 , where 0 < x < 3; o Lithium phosphorus or lithium boron oxynitride based materials, referred to as LiPON and LIBON, containing silicon, sulfur, zirconium, aluminum, or a combination of aluminum, boron, sulfur and / or silicon, and for lithium phosphorus oxynitride based materials, boron; ○Li 1.9 And 0.28 P 1.0 A 1.1 N 1.0 ; ○Lithium oxide, selected from Li7La3Zr2O 12 or Li 5+x La3(Zr x ,A 2-x ) 12 , where A = Sc, Y, Al, Ga and 1.4 ≤ x ≤ 2, or Li 0.35 La 0.55 TiO3 or Li 3x La 2 / 3-x TiO3, where 0≤x≤0.16; ○ Silicate selected from Li2Si2O5, Li2SiO3, Li2SiO6, Li2Si2O6, LiAlSiO4, Li4SiO4, LiAlSi2O6, Li2Si5O 11 ; ○ Anti-perovskite type solid electrolyte Li (3-x) M x / 2 OA, where 0 < x ≤ 3, M is a divalent metal, which is at least one element of Mg, Ca, Ba, Sr, or a mixture of two, three, or four of these elements, and A is a halogen element or a mixed halogen element.
11. A method for manufacturing the anode for a lithium ion battery according to claim 1, comprising the following steps: (a) depositing an anode material on the substrate; (b) depositing a protective coating on the anode material; (c) intercalating the anode material with lithium ions by polarizing the anode material in a solution containing lithium cations.
12. The method according to claim 11, wherein the deposition of the anode material is performed by a vapor deposition technique and / or the deposition of the anode material is performed by a chemical vapor deposition technique.
13. The method according to claim 11, wherein the deposition of the anode material is performed by electrophoresis from a suspension of nanoparticles of at least one anode material, or the deposition of the anode material is performed by immersion.
14. The method according to claim 13, wherein the suspension comprises a primary diameter D 50 Nanoparticles of at least one anode material having a size of 50 nm or less.
15. The method of claim 13, wherein the suspension comprises aggregates of nanoparticles of anode material.
16. The method according to claim 13, characterized in that The anode material is dried, the drying being performed between the end of the electrophoretic deposition and the start of the deposition of the protective coating.
17. The method according to claim 16, characterized in that After drying the anode material is annealed.
18. The method according to claim 17, characterized in that Pressing is performed before and / or concurrently with the annealing.
19. The method according to claim 11, characterized in that The anode material is selected from the group consisting of: -Carbon nanotubes, graphene, graphite; -Lithium iron phosphate, the typical molecular formula is LiFePO4; - Mixed silicon tin oxynitride, with the typical molecular formula Si a Sn b O y N z , where a > 0, b > 0, a + b ≤ 2, 0 < y ≤ 4, 0 < z ≤ 3, also known as SiTON; -Carbon and nitrogen oxides, the typical molecular formula is Si a Sn b C c O y N z , where a>0, b>0, a+b≤2,0 <c<10,0<y<24,0<z<17; -Si x N y Type nitride; Sn x N y Type nitride; Zn x N y Type nitride; Li 3-x M x N-type nitride, wherein when M=Co, 0≤x≤0.5, when M=Ni, 0≤x≤0.6, and when M=Cu, 0≤x≤0.3; or Si 3-x M x N4 type nitride, where 0≤x≤3; - oxides SnO2, SnO, Li2SnO3, SnSiO3, Li with x>=0 and 2>y>0 x SiO y 、Li4Ti5O 12 、TiNb2O7、Co3O4、SnB 0.6 P 0.4 O 2.9 and TiO2, - A complex oxide TiNb2O7 containing 0 to 10% by weight of carbon.
20. The method according to claim 11, wherein the protective coating comprises an electrically insulating material layer deposited by ALD or chemically in a solution, or is selected from a lithium ion conductive solid electrolyte material, and the thickness of the protective coating is 1 nm to 5 nm.
21. A method according to claim 20, wherein after depositing a layer of electrically insulating material or depositing a solid electrolyte layer by ALD or chemically in solution, the deposition of at least one solid electrolyte thin layer is carried out by immersion or by electrophoresis from a suspension of monodisperse nanoparticles comprising at least one solid electrolyte material.
22. A lithium ion battery comprising the anode according to claim 1, or the anode obtainable by the method according to claim 11, and further comprising an electrolyte in contact with the anode, and a cathode in contact with the electrolyte.
23. The battery according to claim 22, characterized in that The electrolyte is a conductor of lithium ions, and the electrolyte is selected from the group consisting of: - all-solid-state electrolytes deposited by vapor deposition, - electrophoretically deposited all-solid-state electrolytes, - an electrolyte formed by a separator impregnated with a liquid electrolyte, - a porous electrolyte impregnated with a liquid electrolyte, - an electrolyte comprising a polymer impregnated with a liquid electrolyte and / or a lithium salt, - An electrolyte formed of a lithium ion conductive solid electrolyte material.
24. The battery according to claim 22, characterized in that The cathode is an all-solid cathode or a porous cathode.
Citation Information
Patent Citations
Method for the production of thin films of solid electrolyte for lithium ion batteries
WO2013064772A1
Method for the production of electrodes for fully solid batteries
WO2013064773A1
Substrate for a photovoltaic cell
WO2013064774A1
Method for producing dense thin films by electrophoresis
WO2013064776A1
Method for manufacturing all-solid-state thin-film batteries
WO2013064779A1